Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan MTs Al-Jam'iyatul Washliyah 18 Tembung - Harahap, Mhd Yusuf; Prayetno, Miftah Suhaila; Siregar, Nova Susanti Br.; Yanti, Dina (Yayasan Pendidikan Islam Akmalia, 2022)
A leader plays an important role an achieving the success and goals of an organization, as well as the principal who has an important rolein the achievement of educational and learning goals. In leading the principal must have profesionalism in order to achieve educational goals, therefore the principal must play a role in the process of planning, monitoring, etc. Improving the quality of schools in one of the goals to be achieved, so to improve the quality of the institution itself the principal must be able to foster and direct teachers to work profesionalilly to improve the quality of student. This study aims to describe the role of principals in improving the quality of education perspective of total quality management concepts. This type of research is the use of qualitative research. MTS Al - Jam'iyatul Kesulitan Tembung head 0f research subjects using interviews, observation, and documentation. The result show thar the principal acts as a manager, innovator, motivator by carrying out several efforts to improve the quality of students at MTS Al - Jam'iyatul Washliyah Tembung 18, arouse student’s interest and motivation to lean and try to improve the character and moral values of students